The BECCS Implementation Gap–A Swedish Case Study - Fuss, Sabine; Johnsson, Filip (Frontiers in Energy Research, 2021)
The IPCC has assessed a variety of pathways that could still lead to an achievement of the ambitious climate targets set in Paris. However, the longer climate action is delayed, the more does this achievement depend on the ability to withdraw CO2 from the atmosphere, applying Carbon Dioxide Removal technologies (CDR). In the assessed pathways, the main CDR technology is Bioenergy combined with Carbon Capture and Storage (BECCS). Even though BECCS has been contested and there are other technologies that could substitute for or complement BECCS, there are many locations globally, which have favorable conditions for BECCS like Sweden with highly productive forests combined with a net growth in biogenic carbon stock. In this study, we analyze the role of BECCS for net-zero targets, assess both the potentials and obstacles for BECCS implementation at national level for the case of Sweden and identify entry points for exploiting the Swedish BECCS potential more effectively. We conclude that in spite of Sweden’s favorable conditions for BECCS in the form of large point sources of biogenic emissions and with BECCS identified by the government as one potential “supplementary measure” allowed to be applied to reach net zero emissions in the target year 2045, there has been little real advancement in planning and preparing for BECCS implementation. There is a significant implementation gap between the actual advancement of BECCS and the ambition for BECCS identified in a recent governmental inquiry. There is an insufficient consideration of incentivization schemes for negative emissions in the light of comprehensive policy packages available for fossil fuel emissions, although these are still too weak. We conclude that to gain acceptance for BECCS, there must be a policy coherence between the cost to emit fossil fuel CO2 and the value put on negative emissions. All in all, more analysis at national level comes forth as a main knowledge gap for closing the implementation gap we observe when comparing climate ambition with CDR deployment – in the case of Sweden in the form of BECCS.